Simple Encircling Scleral Band for Uncomplicated Retinal Detachment - Djatikusumo, Ari; Sjahreza, Emil Fahrinandi; Triwijayanti, Triwijayanti; Taim, Abisyifa Rahma; Ardhia, Seruni Hanna (International Journal of Retina, 2024)
Introduction: Report the surgical and visual outcome of using a narrow band in encircling scleral buckling for selected rhegmatogenous retinal detachment (RRD). Methods: A retrospective case series review of 16 patients with primary RRD treated with encircling scleral buckling using a narrow band 240 (2.5 mm) in KMN Eye Care from June 2018 to June 2020. Results: A total of 16 eyes in 16 patients with RRD underwent encircling scleral buckling with a narrow silicone band 240 (2.5 mm) without any additional tire or sponge. All patients have myopic eyes, with the mean pre-operative best-corrected visual acuity (BCVA) is less than 0.50. The primary success rate of retinal reattachment was 81.25%. Three patients had retinal re-detachment within one month post-surgery, and 2 patients had persistent sub-macular fluid, despite retinal reattachment. In patients with retinal reattachment, the BCVA showed improvement better than 0.5 at 1-month follow-up (9 patients, 69.2%). Spherical equivalent changes before and after scleral buckling were -1.90 D. Conclusion: Narrow encircling scleral buckle surgery can be considered an effective and safe technique in selected RRDs, including anteriorly located, multiple, or invisible retinal breaks. A further, large-size randomized controlled study is needed to confirm its efficacy.